TYPE 2 (SUBRETINAL) NEOVASCULARIZATION IN AGE-RELATED MACULAR DEGENERATION ASSOCIATED WITH PURE RETICULAR PSEUDODRUSEN PHENOTYPE. Issue 3 (March 2016) - Naysan, Jonathan; Jung, Jesse J.; Dansingani, Kunal K.; Balaratnasingam, Chandrakumar; Freund, K. Bailey
Abstract : Purpose: To report the association of pure type 2 neovascularization (NV) in age-related macular degeneration occurring almost exclusively in patients with reticular pseudodrusen. Methods: An observational retrospective cohort study of all eyes receiving antivascular endothelial growth factor therapy for newly diagnosed neovascular age-related macular degeneration by a single practitioner over a 6-year period. Only patients with treatment-naive, pure type 2 NV who also had either pre-neovascular imaging of the study eye or imaging of a nonneovascular fellow eye available to determine baseline characteristics including drusen type and choroidal thickness were incuded. Results: Of 694 patients treated for neovascular age-related macular degeneration, only 8 met the inclusion criteria with pure type 2 NV. Of these, 7 (88%) had exclusively reticular pseudodrusen (5 in the nonneovascular fellow eye, 2 in the study eye before developing NV). Six (75%) patients in the affected neovascular eye and 6 (75%) in the fellow nonneovascular eye had choroidal thickness <120 μ m. Mean follow-up was 46 months (range, 3.0–63.3). Best-corrected vision improved from 20/89 (range, 20/30–20/796) at baseline to 20/60 (range, 20/20–20/399) at last follow-up. Conclusion: Pure type 2 NV is rare in age-related macular degeneration, occurring almost exclusively in patients with reticular pseudodrusen and thin choroids. Abstract : Pure Type 2 neovascularization is rare in age-related macular degeneration. Reticular pseudodrusen are located above the retinal pigment epithelium best visualized by near-infrared reflectance and spectral domain optical coherence tomography. The authors describe the occurrence of pure Type 2 neovascularization in age-related macular degeneration that seems to occur almost exclusively in patients presenting with reticular pseudodrusen compared with other drusen phenotypes.